Speaking of compiling the functional-semantic groups dictionary of verbs of the Belarusian language - Kraskouski, Mikalai I. (Journal of the Belarusian State University. Philology, 2024)
The article presents the results of using the «shuttle» translation method to form the functional semantic group (FSG) of Belarusian verbs based on the verbal vocabulary of the Russian language, presented in the «Explanatory dictionary of Russian verbs. Ideographic description. English equivalents. Synonyms. Antonyms» edited by L. G. Babenko. The potential of the «shuttle» translation method for the formation and addition of parallel FSG of the Belarusian and Russian languages, and the creation of FSG dictionaries has been demonstrated.